A theoretical model of dietary lipid variance as the origin of primary ciliary dysfunction in preeclampsia - Hart, Nancy R. (Frontiers in Molecular Biosciences, 2023)
Preeclampsia of pregnancy is intensely studied as a model for cardiovascular disease partially due to many shared pathophysiologic elements, but also because changes that may develop over decades in cardiovascular disease arise in days with preeclampsia yet resolve rapidly after delivery, thus providing a time lapse view of the development of cardiovascular pathology. The cause of preeclampsia is unknown; presently the only cure is delivery. In recent pathophysiologic reviews, the role of abnormal placentation, a process under the control of Hedgehog and wnt/catenin signaling pathways is emphasized. Presented here is a model which integrates preeclampsia lipidomics, pathophysiology, and epidemiology with the molecular mechanisms of liquid/liquid phase separation in model membrane studies and the known changes in human dietary lipids over the last century to explain how changes in dietary lipids might reduce accessible membrane cholesterol and give rise to the shortened cilia and defects in VEGF, Hedgehog, wnt/catenin signaling which underlie the characteristic placental dysfunction of preeclampsia. This model raises the exciting possibilities of providing a mechanism for non genetic dysfunction in cilia as well as an option to treat and perhaps cure preeclampsia with dietary lipids.